2015
DOI: 10.2169/internalmedicine.54.3413
|View full text |Cite
|
Sign up to set email alerts
|

The Development of Fulminant Type 1 Diabetes during Chemotherapy for Rectal Cancer

Abstract: A 34-year-old man with a history of rectal cancer was receiving oral chemotherapy [tegafur-uracil (UFT) with leucovorin]. He visited our hospital due to nausea and abdominal pain, and his laboratory data revealed the presence of urinary ketones, hyperglycemia and high anion gap metabolic acidosis, and HbA1c level of 6.8%. Accordingly, we diagnosed fulminant type 1 diabetes. The development of fulminant type 1 diabetes during chemotherapy for malignancy is a rare, but potentially fatal condition. Therefore, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…5-fluorouracil, leading to dTTP depletion, is commonly used for cancer chemotherapy (47,48). Both myelosuppression and secondary diabetes are common side effects of 5-fluorouracil therapy (49,50), and a case of fulminant T1D following 5-fluorouracil treatment has recently been reported (51). Although a recent first-phase study of a dUTPase inhibitor indicates good tolerance (52), our findings warrant close monitoring of hematological and metabolic adverse events in these patients.…”
Section: Discussionmentioning
confidence: 68%
“…5-fluorouracil, leading to dTTP depletion, is commonly used for cancer chemotherapy (47,48). Both myelosuppression and secondary diabetes are common side effects of 5-fluorouracil therapy (49,50), and a case of fulminant T1D following 5-fluorouracil treatment has recently been reported (51). Although a recent first-phase study of a dUTPase inhibitor indicates good tolerance (52), our findings warrant close monitoring of hematological and metabolic adverse events in these patients.…”
Section: Discussionmentioning
confidence: 68%
“…Moreover, the destruction of the exocrine part of the pancreatic tissue leads to digestive disorders, and necrosis of the pancreatic islets may bring about glucose intolerance. What is more, chemotherapy may induce diabetes [2], as cancer chemotherapy may decrease insulin sensibility or increase gluconeogenesis. Prognosis of patients with cancer and diabetes is poorer and more complicated, therefore, chemotherapy patients need to be frequently tested for glycaemia [10].…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, only one case with FT1D during chemotherapy with UFT has been reported to date. Adachi et al (20) suggested two possible mechanisms for this development. The first is via immune suppression or immunological reaction, and the second is via the effects of thymidine phosphorylase.…”
Section: Discussionmentioning
confidence: 99%